Spatial aspects of the interpretation of cultural heritage - Sedlacek, Jozef; Matějka, Daniel; Fialová, Zuzana; Klepárník, Radim (Muzeológia a Kultúrne Dedičstvo, 2022)
Creating an exhibition is a multidisciplinary task which, besides the work of the authors of the scenario, copywriters and experts in the given topic, involves also the work of architects and landscape architects. Although the paper reflects on various completed exhibitions, the scenario and form of an exhibition cannot be separated. The paper focuses on spatial aspects of outdoor exhibitions from the perspective of an architect and landscape architect and documents them via various completed exhibitions. In terms of architecture they can be classified upon the aspects of form and content, wherein form covers the spatial, i.e. architectural, design of the exhibition and means, and content covers the quantity, complexity, style and chronology of the information communicated. The motivation for the paper is the need to identify the factors influencing the educational quality of exhibitions that the professionals designing the space and form of exhibitions may use in their practice. This covers predominantly those factors that relate to the designing of spaces where exhibitions take place based on the given scenarios, to which the viewers react rather subconsciously.The method used for the research is a spatial and content analysis of three exhibitions presenting cultural and natural heritage, specifically Hardangervidda National Park in Norway, Kongernes Jelling visitor centre in Denmark, and the National Museum of Rural Life at Wester Kittochside – Scottish National Museum in Great Britain. Factors considered include: the connection to the site – landscape context; authenticity; spatial scenario; and so-called warm-up and cool-down spaces that create atmosphere. A scenario, as in a film, connects the environment and content in a defined chronology. By this research we want to follow up on the trend in museums and exhibitions to present information through powerful narrative storytelling.